2002
DOI: 10.1073/pnas.182189999
|View full text |Cite|
|
Sign up to set email alerts
|

Short-term antigen presentation and single clonal burst limit the magnitude of the CD8+ T cell responses to malaria liver stages

Abstract: Corrections GENETICS.As an addendum for the article ''Discovery of five conserved ␤-defensin gene clusters using a computational search strategy,''

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
93
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 46 publications
11
93
0
Order By: Relevance
“…Although a similar period of prolonged presentation has been reported following Sendai virus infection (12), a number of more recent studies have found the corresponding period to be far more abbreviated (1,3,6). Although our use of relatively large numbers of transgenic T cells may have accentuated the effect of residual presentation, an identical approach showed presentation to last only 3 days after L. monocytogenes infection despite ongoing bacterial replication (6), and even shorter periods of presentation were reported after infection with malaria and vaccinia virus (1, 3).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Although a similar period of prolonged presentation has been reported following Sendai virus infection (12), a number of more recent studies have found the corresponding period to be far more abbreviated (1,3,6). Although our use of relatively large numbers of transgenic T cells may have accentuated the effect of residual presentation, an identical approach showed presentation to last only 3 days after L. monocytogenes infection despite ongoing bacterial replication (6), and even shorter periods of presentation were reported after infection with malaria and vaccinia virus (1, 3).…”
Section: Discussionsupporting
confidence: 54%
“…Initial in vitro studies suggested that naive CD8 ϩ T cells require only brief antigenic stimulation, in some cases as little as 2 h, to enter an autonomous program of division and differentiation (5). At face value, this appears consistent with recent in vivo studies that have shown surprisingly transient levels of Ag presentation after infection with certain viruses, bacteria, and parasites (1,3,6). In these latter studies, Ag presentation could be detected within hours of infection but appeared to be extinguished variously by a day or two after its initiation.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…This is difficult to assess because activated APCs drive the development of CD8 T cell cytolytic activity, which, in turn, would lead to the clearance of Ag. Indeed, recent findings have shown that CD8 T cells that are activated in response to a pathogen such as Listeria monocytogenes or malaria quickly kill APCs (28,29). Such removal of APCs may be an important part of the strategy by which the immune system prevents deletion of primed effector and memory cells.…”
Section: Discussionmentioning
confidence: 99%
“…For CD8 + T cells, it has been shown that antigenic signals beyond an initial period are not required for proliferation (4)(5)(6)(7)(8)(9)(10), thus supporting the notion of early programming of CD8 + T cell expansion (11,12). However, there is also data that CD8 + T cell expansion is correlated with the continued duration of TCR stimulation in the context of both infections and sterile vaccinations (13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: T Cell Receptor-mediated Recognition Of Antigenic Peptidesmentioning
confidence: 92%